2020
DOI: 10.5194/bg-17-2807-2020
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability in the response of phytoplankton and prokaryotes to B-vitamin amendments in an upwelling system

Abstract: Abstract. We experimentally evaluated the temporal (interday and interseason) and spatial variability in microbial plankton responses to vitamin B12 and/or B1 supply (solely or in combination with inorganic nutrients) in coastal and oceanic waters of the northeast Atlantic Ocean. Phytoplankton and, to a lesser extent, prokaryotes were strongly limited by inorganic nutrients. Interday variability in microbial plankton responses to B vitamins was limited compared to interseason variability, suggesting that B-vit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 93 publications
(133 reference statements)
1
24
2
Order By: Relevance
“…1A) showed a marked seasonal variability in the response of phytoplankton and bacteria to inorganic nutrient and/or B12 additions in surface waters, with phytoplankton responding at the beginning and at the end of the productive period. A detailed experimental study by Joglar et al (2020) at a shelf and an oceanic station off this area (stn 3 and stn 6 in Fig.1A) also revealed that phytoplankton and prokaryotes frequently respond to B12 and/or B1 additions. Overall, the magnitude of positive responses in the sampling area after external B12 inputs was relatively small (Barber-Lluch et al, 2019;Joglar et al, 2020), and the patterns of microbial responses appeared to be mostly controlled by the prokaryote taxonomic composition (Joglar et al, 2020).…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…1A) showed a marked seasonal variability in the response of phytoplankton and bacteria to inorganic nutrient and/or B12 additions in surface waters, with phytoplankton responding at the beginning and at the end of the productive period. A detailed experimental study by Joglar et al (2020) at a shelf and an oceanic station off this area (stn 3 and stn 6 in Fig.1A) also revealed that phytoplankton and prokaryotes frequently respond to B12 and/or B1 additions. Overall, the magnitude of positive responses in the sampling area after external B12 inputs was relatively small (Barber-Lluch et al, 2019;Joglar et al, 2020), and the patterns of microbial responses appeared to be mostly controlled by the prokaryote taxonomic composition (Joglar et al, 2020).…”
Section: Introductionmentioning
confidence: 85%
“…3) and by changes in the microbial community composition (Fig. 6), particularly by the relative increase of Synechococcus , which tend to be dominant in oceanic waters in this sampling area (Teira et al ., 2009, Joglar et al ., 2020). Interestingly, Synechococcus is a cyanobacteria that produces and uses pseudocobalamin (Helliwell et al ., 2016), which was not measured in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations